The Impact of Solvent Composition and Copper (Cu) Ion Doping on Dye Anthocyanin on Increasing Dye-Sensitized Solar Cell (DSSC) Efficiency - Novi Dyah Puspitasari; Fahru Nurosyid; Untung Riyadi; Sophia Dewi Nur Anisa; Kusumandari Kusumandari (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
The development of Dye Sensitized Solar Cells (DSSC) is increasing fast because fabrication costs are more affordable than silicon solar cells.  In this study, anthocyanin pigments were used as a natural dye source. Anthocyanins are a group of flavonoids that can be extracted most proficiently in acidic conditions; therefore, variations in the composition of solvents and acids significantly impact anthocyanin yield. The anthocyanin pigments in this study were extracted from dragon fruit peels using a maceration method with variations in methanol composition and the addition of hydrochloric acid or citric acid (3/0; 3/0.5; 3/1). This study aims to improve the efficiency of DSSC by varying the solvent composition and adding Cu ion doping. The characterizations include measurement of absorbance, functional group, and efficiency using UV-Vis Spectrophotometer, Fourier Transform Infrared (FTIR), and current-voltage, respectively.  The results show that anthocyanin dye with a composition of methanol/acid (3/0) and the addition of Cu ion produced the highest absorbance value and efficiency of 0.4102 Ω-1m-1 and 0.016%, respectively.